PENGARUH MODEL COOPERATIVE LEARNING TIPE GROUP INVESTIGATION TERHADAP HASIL BELAJAR PKN SISWA KELAS V SD - Aril, Harsono; Sabri, Tahmid; Marli, Suhardi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to prove whether or not the influence of cooperative learning model of group investigation type and how big influence model of cooperative learning type group investigation on student learning outcomes in learning Citizenship Education in class V SDN 16 Pontianak Kota. This research uses experimental method in the form of quasi experimental design type Nonequivalent Control Group Design. The sample in this research is class V A totaled 27 students. The techniques used in data collection are direct observation and measurement. Data collection tool used is test with type of written test in the form of objective amount 50 problem. Based on calculation of mean statistic of learning result of control class 69,00 and average result of experiment class learning 80,72, obtained tcount = 5,509 and substitute ttable (? = 5%) equal to 2,054, meaning tcount (5,509) > ttable (2.054), then Ha accepted. From the calculation of effect size (ES) obtained 0.98, means learning with cooperative learning model group investigation type gives a high influence on student learning outcomes in learning Citizenship Education in class V SDN 16 Pontianak Kota. Keywords: Model Cooperative Learning type Group Investigation, Learning Outcomes, Citizenship Education